2001
DOI: 10.1080/713663852
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Providing Therapists With Feedback on Patient Progress During Psychotherapy: Are Outcomes Enhanced?

Abstract: Patient-focused research attempts to provide information that answers the question: Is this treatment benefiting this patient? Although several systems have been developed to monitor and provide feedback about a patient's response to psychotherapy, few if any have been tested empirically. The current study divided 609 patients into four groups (two experimental and two control) to determine if feedback regarding patient progress, when provided to a therapist, affected patient outcome and number of sessions att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
218
4
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 366 publications
(231 citation statements)
references
References 18 publications
6
218
4
3
Order By: Relevance
“…Feedback also improves attendance rates, though results are mixed as to whether all clients benefit or just those NOT. Specifically, Lambert et al (2001) found that clients who were NOT in a feedback condition attended significantly more sessions (9.68 vs. 5.03) than NOT clients in a TAU condition. Conversely, Slade et al (2008) found that all clients, not just those NOT, in a feed back condition with clinical support tools at tended 1.5 more sessions compared to TAU.…”
mentioning
confidence: 95%
“…Feedback also improves attendance rates, though results are mixed as to whether all clients benefit or just those NOT. Specifically, Lambert et al (2001) found that clients who were NOT in a feedback condition attended significantly more sessions (9.68 vs. 5.03) than NOT clients in a TAU condition. Conversely, Slade et al (2008) found that all clients, not just those NOT, in a feed back condition with clinical support tools at tended 1.5 more sessions compared to TAU.…”
mentioning
confidence: 95%
“…Warren and Rice (1972) also showed reduced PT by providing four 30-minute support sessions focused on making use of the therapy on offer. Another set of PT studies (e.g., Hawkins, Lambert, Vermeersch & Tuttle, 2004;Lambert et al 2001) investigated the effect of providing therapists with feedback on patient outcomes during therapy, in order to highlight those patients failing to improve and therefore at risk of PT. Lambert et al (2001) found that feedback increased the number of sessions completed for those patients who had been shown to be struggling to improve, but decreased the number of META-ANALYSIS OF PSYCHOTHERAPY ATTENDANCE 7 sessions completed when feedback demonstrated improvement.…”
Section: Narrative Overview Of Strategies To Promote Psychotherapy Atmentioning
confidence: 99%
“…In these published studies each therapist was asked to practice as they routinely do with half their case load while using the OQ-Analyst information with the other half of their case load. In this meta-analytic review of the OQ system data from 6 studies were combined ( n = 6,151) and re-analyzed [26,27,28,29,30,31]. …”
Section: Review Of Evidence Basementioning
confidence: 99%